Managing the Transition to a Circular Economy Action Plans in the Tourism Sector - Segarra-Oña, Marival; Santamarina-Campos, Virginia; Peiró-Signes, Ángel (SpringerBriefs in Business, 2024)
This open access book presents an interdisciplinary analysis of the current status of the circular economy in the tourism sector. This book is presented from the perspective of researchers, policymakers, and industry. Specially aimed at companies in the tourism sector, the book offers valuable information in the field of circular economy, promoting the design/redesign of processes and products. The authors emphasize promoting the development and application of new knowledge and technologies to promote innovation in processes, products, services, and business models, promoting public-private collaboration. With contributions from experts representing varied interests throughout the tourism industry, the book encourages the involvement of economic and social agents to raise awareness of current environmental, economic, and technological challenges.